ประสบการณ์ทางจิตใจของผู้สูงอายุที่ถูกกระทำรุนแรง - กิตติพรรณ ศิริทรัพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
To study the mental experiences of the old aged people from the violence and to study the suffering experiences of the old aged people from the violence by mean of the qualitative research method of phenomena as the tool to understand the experiences of the old aged people from the violence. Data is sampled from the in dept interview and observation in the old aged foster home as the area of study. The data providers consist of 11 persons, 5 males and 6 females in the age range of 60-80 years and the data providers are the close persons of the old aged; family members, social worker and officer of the old aged foster home. The research could be summarized in 2 points as follows: Upon the violence, the old aged people shall have negative feelings i.e. neglected feeling about life, isolate feeling, hopelessness, lament for the past and longing for the future. Those conditions are the emotional conditions experienced by old aged people alone in the old aged foster home based on the data sampling by the researcher. About the mental suffering, from the study, it is found that the old aged people could cope with their troubles in 2 ways. In the beginning, the old aged people usually deny that the negative practice does not really occur and hope that their children would finally change their minds. However, when the violence occurs repeatedly, the old aged people feel confused and find no solutions and have to stay with their family. But when the old aged people have time for reconsidering, the old aged people choose to experience the problems as their fate, forgive, no retribution, making up their mind and let go their troubles in the past which could alleviate the trouble in the mind of the old aged people.